Consumer Protection Regarding the Failure to List Sugar, Salt and Fat Content in Ready-to-Drink Beverages - Anggraini Nur, Yunita; Rahman, Sufirman; Asriati, Asriati (ADVANCED PRIVATE LEGAL INSIGHTS, 2025)
This paper discusses the analysis of forms of consumer protection in terms of not listing the sugar, salt, and fat content in ready-to-drink drinks, and the duties of the health service in supervising business actors who do not list the sugar, salt and fat content in ready-to-drink drink business actors. Using qualitative methods with data from interviews, data processing techniques are carried out using descriptive analysis. The results of the study are forms of consumer protection in terms of not listing the sugar, salt, and fat content in ready-to-drink drinks by accommodating suggestions and input from consumers which will later be conveyed directly to business owners so that these suggestions and input can be considered for consumer health. It is hoped that the task of the government or related agencies to record ready-to-drink drinks that do not comply with PMK.NO. 63 of 2015 to include information on sugar, salt and fat content.